Triboelectric effect of surface morphology controlled laser induced graphene - Choi, Kwang-Hun; Park, Seoungwoong; Hyeong, Seok-Ki; Bae, Sukang; Hong, Jae-Min; Kim, Tae-Wook; Lee, Sang Hyun; Ryu, Seongwoo; Lee, Seoung-Ki (ROYAL SOC CHEMISTRY, 2020)
Here, we studied the triboelectric properties of structurally controlled laser-induced graphene (LIG) to clarify the key factors for improving the energy harvesting performance. With a facile defocusing method, the LIG morphology was modulated in porous LIG, in short carbon fiber combined LIG (SF-LIG) and in long carbon fiber-dominant LIG (LF-LIG). Through correlation analysis of the triboelectrification characteristic according to the material properties of LIG, it was found that asymmetric defects as well as the graphitic-N configuration within the fibrous LIG structure can significantly improve the triboelectric effectiveness by supplying trap sites and lowering the work function, respectively. The vertically aligned fibrous structure also increases the structural contact area, contributing to the improvement in the charge transfer efficiency. As a result, it was demonstrated that the long carbon fiber structure of LF-LIG can improve the performance by 130 times (512 mW m(-2)) compared with porous LIG-based triboelectric nanogenerators (TENGs) (3.9 mW m(-2)). As a feasible application, all LIG-based flexible triboelectric touch sensors are fabricated, which are composed of LF-LIG active matrices (4 x 4) and LIG electrodes through a one-step laser writing process. The demonstrated touch sensor independently addressed each pixel for tracking the location of the human touch, showing self-powering capabilities. This work presents a facile strategy for surface morphology modification of LIGs and investigates their triboelectric charging effect, which might promote the development of practical flexible TENGs for wearable electronic devices.
Keywords: NANOGENERATOR; TRANSPARENT; FIBER; FILMS